THE EFFECT OF COMBINING GOOGLE CLASSROOM AND WHATSAPP ON STUDENT ENGAGEMENT IN ENGLISH CLASS - Rosi Anjarwati; Lailatus Sa'adah (Universitas Islam Lamongan, 2022)
Information and Communication Technology (ICT) has developed rapidly so that people should adjust themselves to the development. In education field, the use of technology is very needed in today era. The condition of the world due to the Pandemic of COVID-19 in the past two years forced teacher and students to have long-distance learning virtually with the help of ICT. This current study tries to explore the effect of using Google Classroom combining with WhatsApp in teaching English at SMK Tamansiswa Mojoagung on three dimensions of student engagement. This study is quasi-experimental with post-test only design since the purpose of the study is to examine whether there is a significant effect of combining Google Classroom and WhatsApp on student engagement. The research instrument used is questionnaire to get the data about student engagement in three dimensions: behavioral, cognitive, and emotional engagement based on their self-assessment. Analyzing by using SPSS software, the results reveal that there is a significant difference of student behavioral engagement between students in two groups of different media used. On the other hand, it is found that there is no significant difference of cognitive and emotional engagement.